2020
DOI: 10.1093/ageing/afz181
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of the perspectives of older people in the Scottish Highlands on the management of their chronic pain

Abstract: Background Although there is evidence of suboptimal outcomes in older people with chronic pain, little emphasis has been placed on those in remote and rural settings. Objective To describe the perspectives of older people in the Scottish Highlands on their chronic pain management. Design Cross-sectional survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Older adults (defined as those aged 75 years and over) living within remote and rural areas of NHS Highland who are experiencing chronic pain (defined as pain lasting more than 12 weeks) who participated in the previous survey-based research project [ 18 ] and indicated on the questionnaire returned that they were willing to take part in further research were invited to participate in the interviews. Those willing were mailed the participant information sheet and asked to complete a consent form and provide details of the best days and times of the week for the interview.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults (defined as those aged 75 years and over) living within remote and rural areas of NHS Highland who are experiencing chronic pain (defined as pain lasting more than 12 weeks) who participated in the previous survey-based research project [ 18 ] and indicated on the questionnaire returned that they were willing to take part in further research were invited to participate in the interviews. Those willing were mailed the participant information sheet and asked to complete a consent form and provide details of the best days and times of the week for the interview.…”
Section: Methodsmentioning
confidence: 99%
“…Those experiencing chronic pain were significantly higher users of healthcare resources and living in more deprived areas. Pain was most commonly managed by a GP using paracetamol alone or in combination with opioids and other analgesics, with few respondents reporting using non-pharmaceutical therapies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%